Parapharyngeal Neuroglial Heterotopia: A Case Report - Reza Saeidi; Mahmoud Hajipour; Ahmad Shah Farhat; Ashraf Mohammadzadeh; Fatemeh Serati (Mashhad University of Medical Sciences, 2022)
Background: Neonatal neck masses usually fall into three categories: developmental, inflammatory, and neoplastic. Malignant neck masses are rarely observed in neonates; nonetheless, If malignancy is suspected, the patient should be evaluated urgently. In this paper, we describe the case of a neonate with a very rare congenital neck tumor, nasal glial heterotopia, which was first described by Reid in 1852, and only 20 cases have been reported in the parapharyngeal space in an article published in 2005.Case report: This case report presents a 3-month-old girl misdiagnosed with cystic hygroma at one month. She finally underwent surgery due to the progress of symptoms, airway obstruction, and mass neck enlargement. The pathological diagnosis confirmed a rare case of parapharyngeal neuroglial heterotopia.Conclusion: One case of glial heterotopia of the parapharyngeal space was included and presented in the present study. Glial heterotopias are very rare in the parapharyngeal space. Histopathology and immunohistochemistry are essential to diagnose this lesion.